A LITERATURE REVIEW ON EUROPEAN INTEGRATED BORDER MANAGEMENT - Yao, Xuedan (International Journal of Innovative Technologies in Social Science, 2022)
In the wake of the Schengen Agreement, the EU has assumed the role of maintaining European security, and border integration management has been ranked among the top priorities for the EU. It is necessary to improve border integration management to advance the integration process. Despite this, border integration management in the EU has been challenging, particularly since the refugee crisis of 2015. This article analyzes the current directions and trends of relevant research on border integration management in the EU. Three main areas of research on border integration management are currently being conducted: migration policy, border control agency, and border integration problems. The study concluded that theoretical and organizational analysis need to complement border management research.